Listeria Monocytogenes as Contaminant of Food Derived from Animal (Foodborne Disease) - Ariyanti, Tati (Indonesian Bulletin of Animal and Veterinary Sciences, 2010)
Listeria monocytogenes often contaminates food derived from animal and serves as pathogenic bacteria for animals and human. The outbreaks were related with the consumption of food derived from animals such asÂ  meat, milk, egg, seafood and its product that poorly cooked. Human listeriosis could be transmitted by direct contact with infected animal. The disease often is asymtomatic and widely distributes in the world. The mortality rate reaches to 30%. The bacteria is important because of the widespread in the environment, tolerant to acid, hot or salt environments, forms a biofilm layer and produces virulent factor (listeriolisin O/LLO). The bacteria can grow at 4Â°C or in the frozen food. Appropriate handlings of animals and their products are important to prevent from L. monocytogenes contamination. Key words: Foodborne disease, L. monocytogenes, food derived from animal, listeriolisin O